PENGARUH KARAKTERISTIK CEO, KOMISARIS INDEPENDEN, DAN KUALITAS AUDIT TERHADAP PENGHINDARAN PAJAK - Doho, Sisilia Zealion; Santoso, Eko Budi (Media Akuntansi dan Perpajakan Indonesia, 2020)
This research aims to determine the influence of CEO narcissism,CEO tenure, independent commissioner and audit quality against tax avoidanceon companies registered in the non-financial sector. CEO narcissismwas measured by scoring the photo of CEO in annual report, CEO tenurewas measured from the length of the CEO’s term, independent commissionerwas measured by the number of independent commissioners dividedby the total commissioner within the company. While audit quality wasmeasured using a dummy variable where score 1 was given was for companiesaudited by the big four accountant firms and 0 for companies auditedby non-big four accountant firms meanwhile the tax avoidance was measuredusing an ETR proxy. This research used secondary data in fom ofannual reports of non-financial sector companies listed on the IndonesiaStock Exchange in the year 2016–2018. The results of this research showthat: (1) the CEO of narcissism has no effect on the tax avoidance, (2) theCEO tenure has a significant positive influence on the tax avoidance, (3)independent commissioner has no influence on the tax avoidance, and (4)audit quality has a significant positive influence on the tax avoidance.